Response of Coastal Shewanella and Duganella Bacteria to Planktonic and Terrestrial Food Substrates - Zhao, Li; Brugel, Sonia; Ramasamy, Kesava Priyan; Andersson, Agneta (Frontiers in Microbiology, 2022)
Global warming scenarios indicate that in the subarctic regions, the precipitation will increase in the future. Coastal bacteria will thus receive increasing organic carbon sources from land runoff. How such changes will affect the function and taxonomic composition of coastal bacteria is poorly known. We performed a 10-day experiment with two isolated bacteria: Shewanella baltica from a seaside location and Duganella sp. from a river mouth, and provided them with a plankton and a river extract as food substrate. The bacterial growth and carbon consumption were monitored over the experimental period. Shewanella and Duganella consumed 40 and 30% of the plankton extract, respectively, while the consumption of the river extract was low for both bacteria, ~1%. Shewanella showed the highest bacterial growth efficiency (BGE) (12%) when grown of plankton extract, while when grown on river extract the BGE was only 1%. Duganella showed low BGE when grown on plankton extract (<1%), and slightly higher BGE when grown on river extract (2%). The cell growth yield of Duganella was higher than of Shewanella when grown on river extract. These results indicate that Duganella are more adapted to terrestrial organic substrates with low nutritional availability, while Shewanella are adapted to eutrophied conditions. The different growth performance of the bacteria could be traced to genomic variations. A closely related genome of the Shewanella was shown to harbor genes for sequestration of autochthonously produced carbon substrates, while the Duganella contained genes for degradation of relatively refractive terrestrial organic matter. The results may reflect the influence of environmental drivers on bacterial community composition in natural aquatic environments. Elevated inflows of terrestrial organic matter to coastal areas in subarctic region would lead to increased occurrence of bacteria adapted to degradation of complex terrestrial compounds with a low bioavailability.